2003
DOI: 10.1016/s0736-5748(03)00072-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuropeptides in anterior pituitary development

Abstract: Recent studies using biotechnological methods have achieved significant advances in our knowledge of molecular mechanisms underlying pituitary gland development and the differentiation of pituitary cytotypes. A large number of neuropeptides have been reported in the adult pituitary gland as well as in the central and peripheral nervous system. The early presence of neuropeptides during pituitary development is reviewed here. Neuromedin U (NmU), galanin and the polypeptide 7B2 have been localised to different e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 127 publications
1
9
0
Order By: Relevance
“…Electron microscopy studies revealed NMU-like immunoreactivity in some thyrotropes and most corticotropes of the rat pituitary gland. NMU is colocalized with galanin and ACTH in the same secretory granules (Cimini et al, 1993; for review see Malendowicz, 1998; Cimini, 2003). …”
Section: Expression Of Nmu and Nms And Their Receptors In The Hypothamentioning
confidence: 99%
See 1 more Smart Citation
“…Electron microscopy studies revealed NMU-like immunoreactivity in some thyrotropes and most corticotropes of the rat pituitary gland. NMU is colocalized with galanin and ACTH in the same secretory granules (Cimini et al, 1993; for review see Malendowicz, 1998; Cimini, 2003). …”
Section: Expression Of Nmu and Nms And Their Receptors In The Hypothamentioning
confidence: 99%
“…In developing rat NMU-immunopositive cells appear in anterior pituitary at day E15 (Cimini, 2003). Their number increases at day E20 and then decreases.…”
Section: Expression Of Nmu and Nms And Their Receptors In The Hypothamentioning
confidence: 99%
“…Protein 7B2 is produced as an intracellular precursor of 25-29 kDa, which is converted into a secreted form of 18-21 kDa (Mbikay et al, 2001). The function of protein 7B2 has been related to cell secretion regulation and signal transduction (Cimini, 2003). CPH, also known as enkephalin convertase, is involved in the biosynthesis of bioactive peptides, which are probably involved in the removal of residual COOH-terminal arginine or lysine residues from peptide hormone precursors during their processing in secretory granules (Dalle Ore et al, 1999).…”
Section: Identification Of Hormone-related Genesmentioning
confidence: 99%
“…A large number of important biomolecules in the pituitary, such as neurotransmitters and neuropeptides including growth and differentiation factors, are involved in cell regulation (Cimini, 2003). Several neuropeptides are found in the different endocrine cells of pituitary: substance P, neuromedin B, neuropeptide Y, neuromedin U, galanin and the polypeptide 7B2 (Cimini, 2003;Mbikay et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation